Postnatal weight loss and exclusive breastfeeding in newborn - Arezoo Haseli; Marzieh Bagherinia; Lida Menati; Sareh Farshadfar; Fatemeh Karpasand; Zahra Karimian (BMC Pediatrics)
Abstract Background Despite global efforts to promote breastfeeding, the rate of exclusive breastfeeding (EBF) has remained stagnant in recent decades. Identifying factors that influence EBF is crucial. Therefore, this study aimed to investigate weight patterns and their association with EBF in newborns, specifically comparing infants with and without excessive weight loss. Methods This retrospective, descriptive-analytical study included 1101 healthy, singleton infants who attended health centers in Kermanshah, Iran, between Nov to Des 2024. All nutritional information and weight of infant from birth to 2 years old were collected in the questionnaire. The data was analyzed using descriptive statistical methods and analytical tests using the SPSS software at significance level less than 0.05. Results In this study, medical records of 1,101 infants were analyzed. The mean birth weight was 3,282 g (SD = 393), and the mean gestational age was 38.52 weeks (SD = 1.38). During the first 3–5 days after birth, the mean weight loss among infants was 131 g (SD = 92), equivalent to 4.01% ± 3.30% of their birth weight. Weight loss was higher in late preterm infants compared to term infants (91.6% vs. 84.6%, r = 0.233) and in cesarean deliveries compared to vaginal deliveries (81.5% vs. 71.4%, r = 0.455). Infants who lost more than 5% of their birth weight had a lower mean weight at 24 months compared to those who lost ≤ 5% (11,942 ± 1,646 g vs. 12,484 ± 1,790 g; p < 0.001). Exclusive breastfeeding (EBF) rates declined sharply in infants who lost > 5% of their birth weight, dropping from 97% during the first 3 days after birth to 59.3% by 6 months. In contrast, EBF rates remained relatively stable in infants who lost ≤ 5% (57.8% in the first 3 days vs. 49.2% at 6 months). Conclusion Greater early postnatal weight loss combined with failure to regain birth weight by day 10 is associated with reduced EBF duration and lower infant weight at two years. These findings suggest that interventions to minimize excessive postnatal weight loss and promote timely weight regain may promote EBF and improve long-term infant growth.